Ministry Of Finance Decree No. 91 of the Year 2024 Concerning the Rules Governing the Enforcement of Law No. 9 of the Year 2024 Concerning Expediting the date of Entitlement to the periodic Raises, Granting a Special Raise to the Workers Non-Addressed by the Civil Service Law, Increasing the Additional Incentive Payable to the State Civil Servants, Giving a Special Grant to the Workers of the Public Sector Companies and Public Business Sector Companies And Increasing the Civil and Military Pensions = وزارة المالية قرار رقم 91 لسنة 2024 بشأن قواعد تنفيذ أحكام القانون رقم 9 لسنة 2024 بتعجيل موعد استحقاق العلاوات الدورية ومنح علاوة خاصة لغير المخاطبين بقانون الخدمة المدنية وزيادة الحافز الإضافي للعاملين بالدولة وبتقرير منحة خاصة للعاملين بشركات القطاع العام وقطاع الأعمال العام وزيادة المعاشات المدنية والعسكرية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic